Palf-crete / Muhammad Aiman Hafiz Ab. Halim, Khairul Ammar Hakimi Khairulmuzzamil and Muhammad Shareef Nahoor Aziz - Ab. Halim, Muhammad Aiman Hafiz; Khairulmuzzamil, Khairul Ammar Hakimi; Aziz, Muhammad Shareef Nahoor (2020)
Natural fibres appear to be outstanding materials which are viable substitute for the expensive and non –renewable synthetic fiber. Pineapple Leaf Fiber (PALF) has good potential as reinforcement in foamed concrete. In this study, PALF of specific aspect ratio will randomly be dispersed in foamed concrete mortar for the preparation of test specimens and tested with compressive strength test, flexural strength test and indirect splitting tensile strength test. Tests used are all based on ASTM Standards.